MUKHTALIF AL-ḤADĪṠ TENTANG KEPEMIMPINAN PEREMPUAN DALAM RUANG PUBLIK MODERN - Nurfaisah Nurfaisah; Muhammadiyah Amin; La Ode Ismail Ahmad (DIRAYAH : Jurnal Ilmu Hadis, 2026)
The issue of women’s leadership in Islam continues to be a subject of debate, particularly concerning the prophetic tradition stating that a people will not prosper if they entrust their affairs to a woman. This ḥadīth is often understood as a prohibition against women assuming leadership roles, while modern political realities demonstrate that women have actively participated in public and state leadership. This study aims to analyze the ḥadīth concerning women’s leadership through the approach of mukhtalif al-ḥadīṡ and to examine its relevance within the context of the modern public sphere. This research is a library research employing a ḥadīth approach and contextual analysis. The data sources consist of canonical ḥadīth collections, classical commentaries, and contemporary literature related to gender and women’s leadership. The findings reveal that the ḥadīth regarding the prohibition of women’s leadership is classified as ṣaḥīḥ; however, scholars differ in interpreting it. Some scholars understand the ḥadīth textually as a general prohibition, while others interpret it contextually based on the historical background related to the leadership of the Persian emperor’s daughter. The mukhtalif al-ḥadīṡ approach demonstrates that contextual interpretation is more relevant in addressing the dynamics of modern society, thereby allowing women’s leadership as long as it fulfills the principles of justice, competence, and public benefit.